2016
DOI: 10.15835/buasvmcn-asb:11429
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals and Dietary Supplements Extracted from Mare’s Milk

Abstract: Mare's milk is similar to human breast milk and has valuable therapeutic properties. For this reason, Europeans are increasingly interested in discovering its benefits and how the chemical composition of horse milk differs from that of other species. This interest is reflected in the number of new farms selling mare's milk around the world as this milk is the most similar to human milk. Mare's milk is considered to be highly digestible, rich in essential nutrients and whey protein, which makes it very suitable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The growing interest in this type of milk was aroused due to the similarity of its chemical composition to that of human milk. Mare's milk products are very common in Russia and Central Asia throughout Mongolia [110]. Moreover, more frequent use of mare milk as a dietary supplement was also shown for elderly citizens, convalescent individuals, and mainly for children allergic to cow milk [111].…”
Section: Discussionmentioning
confidence: 99%
“…The growing interest in this type of milk was aroused due to the similarity of its chemical composition to that of human milk. Mare's milk products are very common in Russia and Central Asia throughout Mongolia [110]. Moreover, more frequent use of mare milk as a dietary supplement was also shown for elderly citizens, convalescent individuals, and mainly for children allergic to cow milk [111].…”
Section: Discussionmentioning
confidence: 99%
“…Before addition of chymosin authors advocated adding starter cultures as they suppress undesirable bacteria, and produce lactic acid, which increase curd firmness and lower pH to 5.1 (optimal for camel chymosin). Mare milk has also been used in cosmetics such as shampoo, shower gel, body cream, soap, hand cream (Stuparu et al, 2016). However, the main use of horses in Europe remains to be recreational riding and horse racing (Liljenstolpe, 2009).…”
Section: Different Products From Mare Milkmentioning
confidence: 99%
“…Jirillo et al (2010) found that mare milk strengthens the immune system. It was explained by a high content of albumin and globulin in the milk, which are building materials for antibodies (Stuparu et al, 2016).…”
Section: Health Benefits Of Mare Milk and Qymyzmentioning
confidence: 99%
“…In Europe, the dairy equine industry is thriving in France where it was started with the animal diversity preservation project [ 6 ], and it is developing little by little in many areas of the world including Italy, Greece, Germany, Mongolia, Kazakhstan, Kirgizstan, and China [ 7 , 8 , 9 ]. The interest toward equine milk and derivatives results from the compositional peculiarities of equine milk and their potential health-promoting properties, which have found applications in both human food [ 5 , 7 , 10 , 11 ] and non-food sectors [ 12 ]. In the food sector, the use of equine milk supports nutrition and treatment of children with allergies to bovine milk protein [ 7 , 13 ], children with multiple food allergies [ 10 ], and children with food protein-induced enterocolitis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equine milk is used also in the nutrition of adults with immunocompromised or debilitated systems [ 7 , 13 ]. In the non-food sector, equine milk works well as a good ingredient in cosmetic products [ 12 ]. Such a specific utilization of equine milk is determined by its beneficial content of water, fat, and allergens including lactose [ 15 ], which is much closer to humans than to bovine milk [ 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%